PENGEMBANGAN MODEL REALISTIC MATHEMATICS EDUCATION (RME) DALAM PENINGKATAN PEMBELAJARAN MATEMATIKA BAGI MAHASISWA PEDIDIKAN GURU SEKOLAH DASAR - Wahyudi - (JURNAL PEDAGOGIK PENDIDIKAN DASAR, 2020)
The purpose of this study are to describe: (1) Realistic Mathematics Education (RME) in improving Mathematics learning to the students in Department of Primary Schools Teacher Education, Faculty of Teacher Training and Education, Sebelas Maret University (PGSD FKIP UNS) campus of Kebumen, (2) reconstruction the curriculum of Mathematics Education  subject in the Department of PGSD FKIP UNS campus of Kebumen based on Realistic Mathematics Education (RME), and (3) the construction of teaching material books of Mathematics Education subject in the Department of PGSD FKIP UNS campus of Kebumen based on Realistic Mathematics Education (RME). The research method is Classroom Action Research (CAR) with cyclical model, involving four steps simultaneously as follows: (1) planning, (2) action, (3) observation, and (4) reflection. Subject of this research was all students at the fourth semester in Department of PGSD FKIP UNS Campus of Kebumen in the academic year 2014/2015, totaling 71 students. Techniques of collecting data used by the researcher were observation, interview, and test. Validity of data used in this research was the techniques of triangulation of source, method, and theory. Techniques of analyzing data was descriptive- qualitative data analysis, including data reduction, data display, and drawing conclusion or verification. The results of this research are: (1) the Realistic Mathematics Education (RME) model can improve Mathematics learning to the students in the Department of PGSD FKIP UNS campus of Kebumen, (2) reconstruction the curriculum of Mathematics Education subject in the Department of PGSD FKIP UNS campus of Kebumen, and (3) the teaching material books of Mathematics Education subject in the Department of PGSD FKIP UNS campus of Kebumen based on Realistic Mathematics Education (RME).